2021
DOI: 10.1007/s00109-021-02065-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and antioxidative effects of pioglitazone in brain tissue adjacent to the ischemic core are mediated by PI3K/Akt and Nrf2/ARE pathways

Abstract: The present study elucidates the neuroprotective mechanisms of the PPARγ (peroxisome proliferator-activated receptor γ) agonist pioglitazone in survival of ischemic neurons following middle cerebral artery occlusion with reperfusion (MCAO). Intracerebroventricular infusion of pioglitazone over 5 days before and 24 or 48 h after MCAO alleviated neurological impairments, inhibited apoptosis 24 h, and activated the PI3K/Akt pathway along with increased phosphorylation of Akt (ser473) and GSK-3β (ser9) in the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…This is inconsistent with the results of other studies showing that EGCG acted as a promoter of antioxidant and anti-inflammatory properties by activating Nrf2 and HO-1 exression. 44 , 46 , 47 One reason for this may be that 6-OHDA-induced oxidative stress and inflammatory response could further activate the protein expression of Nrf2, HO-1, and PPARγ, whereas EGCG treatment restored the cells to a level of low oxidative stress and inflammation. Another reason for the discrepancy of our results might be related to the difference of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…This is inconsistent with the results of other studies showing that EGCG acted as a promoter of antioxidant and anti-inflammatory properties by activating Nrf2 and HO-1 exression. 44 , 46 , 47 One reason for this may be that 6-OHDA-induced oxidative stress and inflammatory response could further activate the protein expression of Nrf2, HO-1, and PPARγ, whereas EGCG treatment restored the cells to a level of low oxidative stress and inflammation. Another reason for the discrepancy of our results might be related to the difference of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified a significant role for pathways of programmed cell death that can ultimately control cell survival and cognitive impairment during MS [46,61,128,130,132,134,[200][201][202] (Table 1). Programmed cell death pathways that involve autophagy, apoptosis, pyroptosis, and ferroptosis can influence cell survival during inflammation [34,39,66,73,74,85,87,[203][204][205][206][207][208][209][210][211][212][213], oxidative stress [10,45,77,86,89,93,119,185,[214][215][216][217][218][219], ischemia [219][220][221][222][223], and mitochondrial dysfunction [32,…”
Section: Autophagy Apoptosis Pyroptosis and Ferroptosis Involvement I...mentioning
confidence: 99%
“…Indeed, the Akt pathway and inhibitory Ser 9 phosphorylation of GSK-3β were shown to prevent miPTP opening and mitochondrial swelling in response to excessive ROS production ( Juhaszova et al, 2004 ). GSK-3β further counteracts Akt/NRF-2-mediated anti-oxidative gene transcription (such as HO-1 Zhao et al, 2021c ), elicits the joint inactivation of the key TCA enzyme PDH with TPKI and inhibits mitochondrial complex I-IV and ATP synthesis. The impaired mitochondrial function, in turn, exacerbates ROS generation (see Yang et al, 2017 ; Figure 2 ).…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%